2010
DOI: 10.3928/15428877-20100215-35
|View full text |Cite
|
Sign up to set email alerts
|

Pars Plana Vitrectomy and Intravitreal Liposomal Amphotericin B in the Treatment of Candida Endophthalmitis

Abstract: Candida endophthalmitis is a common cause of fungal endophthalmitis. A case of bilateral endogenous endophthalmitis caused by Candida albicans without candidemia in an otherwise healthy 77-year-old man was reported. The patient underwent bilateral pars plana vitrectomy and intravitreal liposomal amphotericin B injections in addition to systemic fluconazole therapy. Postoperatively, a significant decrease of inflammation and resolution of abscesses were observed in both eyes. Vision improved in the left eye but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…On histologic examination, increasing grades of vitreal inflammation and retinal damage were detected along with increasing doses, but there was no significant difference among eyes with 3 different agents [14]. Koç et al [5] reported clinical application of intravitreal L-AMB injection for the first time in 2010. They reported a case of bilateral Candida albicans endophthalmitis successfully treated with intravitreal 5 μg/0.1 mL L-AMB injection combined with vitrectomy in addition to systemic fluconazole therapy [5].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…On histologic examination, increasing grades of vitreal inflammation and retinal damage were detected along with increasing doses, but there was no significant difference among eyes with 3 different agents [14]. Koç et al [5] reported clinical application of intravitreal L-AMB injection for the first time in 2010. They reported a case of bilateral Candida albicans endophthalmitis successfully treated with intravitreal 5 μg/0.1 mL L-AMB injection combined with vitrectomy in addition to systemic fluconazole therapy [5].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Traditionally, amphotericin B (AMB) has been used as a first-line drug for intravitreal injection of antifungal drugs, but there are still concerns about retinal toxicity [4]. Recently, the usefulness of intravitreal injection of liposomal AMB (L-AMB), which has significantly improved systemic toxicity profile while retaining an antifungal effect compared to conventional AMB deoxycholate (AMB-D), for the treatment of OC caused by Candida albicans has been reported [5,6]. However, there is no report of intravitreal L-AMB injection for the treatment of OC caused by Candida glabrata.…”
Section: Introductionmentioning
confidence: 99%
“…C. retinitis can be treated in two ways: Liposomal amphotericin B formulation combined with flucytosine is used for advances lesions, cases with less serious severity can be treated with fluconazole. The recommended duration of therapy is at least 4 to 6 weeks [15]. When our case had developed sepsis, findings shown that there are no growing candida species in the blood cultures, however, we initiated empirically fluconazole along with antibacterial therapies.…”
Section: Case Descriptionmentioning
confidence: 91%
“…Intravitreous injection of 5 to 10 g of amphotericin B is a widely used treatment for fungal endophthalmitis. While amphotericin B is an irritant, intravitreal liposomal amphotericin B is well tolerated in monkey and rabbit eyes and has been used in the treatment of Candida endophthalmitis (16,27,28). Another broad-spectrum antifungal agent administered intravitreally for treatment of fungal endophthalmitis is voriconazole, which inhibits the fungal enzyme cytochrome P450 demethylase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to voriconazole, fluconazole also penetrates well into the vitreous, and both agents have been effective in treating fungal endophthalmitis through intravenous administration (14,15). Intravitreal injection of liposomal amphotericin B, which has less toxicity than amphotericin B, was used to treat a patient with bilateral endogenous Candida endophthalmitis (16).…”
mentioning
confidence: 99%